Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1177/00220345840630061801
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation as a Possible Cause of Benzoyl Peroxide Toxicity in Rabbit Dental Pulp—A Microsomal Lipid Peroxidation in vitro

Abstract: The toxicity of composite resin on rabbit dental pulp was investigated biochemically. A microsomal fraction of rabbit dental pulp was incubated with each of the components of composite resins, and the formation of peroxide was determined by the thiobarbituric acid reaction. Benzoyl peroxide (BPO), the most widely used catalyst, was the most effective on peroxidation, but monomers were not. Cations such as Cu2+ or Fe2+ were required for acceleration of this reaction. Authentic polyunsaturated fatty acids and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 24 publications
(12 reference statements)
0
35
0
Order By: Relevance
“…This can be explained by the more hydrophilic character of HEMA, which has an additional hydroxyl group compared with TEGDMA. The higher cytotoxicity of TEGDMA compared with HEMA could further be explained by its ability to interact with the lipid bilayer of cell membranes in a surfactant-like manner 66) and/ or by its ability to cause lipid peroxidation in vitro 67,68) . Both membrane effects can cause cell death 69) .…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the more hydrophilic character of HEMA, which has an additional hydroxyl group compared with TEGDMA. The higher cytotoxicity of TEGDMA compared with HEMA could further be explained by its ability to interact with the lipid bilayer of cell membranes in a surfactant-like manner 66) and/ or by its ability to cause lipid peroxidation in vitro 67,68) . Both membrane effects can cause cell death 69) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, permanent 3T3 cells were less sensitive to the cytotoxic alterations owing to these two substances in comparison to primary cultures. It was documented by Terakado et al, 30 using the microsomal fraction derived from the rabbit dental pulp, that the initiator DBPO alters biological membranes. This indicates that permanent 3T3 cells are possibly less affected by membrane alterations than the primary cells applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, membrane injuries caused by Bis-GMA-induced peroxide formation as well as a high hemolytic activity of Bis-GMA were found. 30,33 Although these bulky and large basic monomers cannot diffuse through the set resin composites and are hardly water-soluble, small amounts of these monomers have been identified in aqueous extracts from polymerized specimens of various resin composites. 2 It may be concluded that these significantly cytotoxic substances should not cause acute damages of the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TEGDMA can induce lipid peroxidation of microsomes. Furthermore, this comonomer also exhibited surfactant-like potency which may cause detrimental solubilization of the lipid bilayer of cell membranes (Terakado et al, 1984;Fujisawa et al, 1988). Geurtsen et al ( 1998a) investigated cytotoxic effects of 35 single monomers and additives of composite resins in permanent 3T3 cells and three primary human oral fibroblast cultures (Table 1).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%